OBSTETRIC TACTICS AND PERINATAL OUTCOMES IN CHORIOAMNIONITIS - Кравченко, Елена Николаевна; Куклина, Лариса Владимировна (Mother and Baby in Kuzbass, 2022)
The problem of chorioamnionite remains relevant and discussed in recent decades, so new terms have been proposed, diagnostic criteria have been identified. The proposed changes regarding chorioamnionitis relate more to perinatal aspects, in particular, to the management of newborns from pregnant women with suspected intrauterine infection and from mothers with chorioamnionitis. The main direction: to observe, not to treat, born in a satisfactory condition of full-term and premature ines on outcomes in infants exposed to intrauterine infection or inflammation. Improving the accuracy of clinical diagnosis of intrauterine infection should improve both the quality and reproducibility of data from future studies.